Educating through Ritual: Rokat Bar-Lobaran as the Educational Heritage of the Madurese Society - Arman; Rahmat Hidayat (Journal of Social Studies and Education, 2025)
This research aims to reveal the stages of implementing the Rokat Bar-Lobaran ritual as a means of instilling educational value in society. The Bar-Lobaran rocket is a hereditary tradition that is carried out twice a year, namely during the transition period of the dry season to the rainy season and vice versa. The method employed is a qualitative approach, utilizing a case study design. Data was collected through direct observation, in-depth interviews with ritual performers and locksmiths, and documentation. Data analysis follows the Miles and Huberman model, which involves data reduction, data presentation, and conclusion. The results of the study reveal that this ritual comprises several main stages, namely preparation, Rokat Ngoro' Somor, Rokat Accem Raja, and the culmination of Rokat Bar-Lobaran, which is carried out in the Kakandhalia Cave. Each stage is led by a community leader who inherits a special customary title, and each process contains educational values such as responsibility, cooperation, cultural preservation, and spirituality. Value instilling is carried out symbolically and practically through community participation in every stage of the ritual. This research demonstrates that Rokat Bar-Lobaran is not only a cultural heritage but also a vehicle for educational values rooted in local wisdom that remains relevant in the context of modern society.